Variations of physical and mechanical properties of concrete with the height - Sadoun, Mohamed; Zemri, Cheikh; Benmahdi, Khaled; Rahal, Nacer (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: Concrete, mortar, and cement pastes are materials that have become central in various fields of construction, structures, and civil engineering. About 7 billion cubic meters of concrete are implemented. Concrete is generally considered a homogeneous material, but that is not always the case given its rheological behavior, which can be due to heterogeneous phenomena of segregation and bleeding.Methods: The study tested a concrete column's physical and mechanical characteristics and deformation in elevation. The tests included measuring absolute and apparent density, porosity, capillary absorption, permeability, speed of propagation, compressive strength, and static and dynamic modulus of elasticity. For this purpose, the standards of non-destructive testing (sclerometer, ultrasound, etc.) were used to take the average of a series of points located at different levels of the element to be tested.Results: The results indicate that changes in the column's height affect its physical and mechanical properties, either increasing or decreasing them (such as porosity, absorbency, permeability, compressive strength, and the static and dynamic modulus of elasticity). These changes are influenced by various factors, including the inherent properties of the concrete implementation (such as vibration and curing) and the climate conditions during construction.Conclusion: The findings of this study emphasize the importance of a nuanced approach to testing and evaluating variations in concrete properties by taking into account the multifaceted impact of changes in column height.
Keywords: concrete; porosity; compressive strength; modulus of elasticity; permeability; elevation